NRTI Sparing Therapy in Virologically Controlled HIV-1 Infected Subjects: Results of a Controlled, Randomized Trial (Probe). (1st May 2016) - Maggiolo, Franco; Di Filippo, Elisa; Valenti, Daniela; Serna Ortega, Paula; Callegaro, Annapaola
Abstract : Abstract: Dual treatments could help clinicians to avoid drawbacks and toxicities due to the nucleosidic backbone, while maintaining the efficacy and convenience of robust combination antiretroviral therapy (cART). We explored the combination of rilpivirine plus boosted darunavir (DRV) as an option when switching from standard cART in patients who are virologically suppressed. In this randomized, open-label, proof-of-concept, noninferiority trial, we recruited patients aged 18 years or older with chronic HIV-1 infection and on a stable, effective (>6 months) protease inhibitor–based cART including a nucleosidic backbone. The primary endpoint was noninferiority of the virological response between treatment groups, according to FDA snapshot approach. Sixty patients were randomly allocated to dual treatment with rilpivirine plus boosted DRV or to continue their ongoing triple treatment. Noninferiority was shown at the prespecified level of −12% both at 24 and 48 weeks. At week 24, 100% of patients in the dual arm presented a blood HIV-RNA level <50 copies per milliliter compared with 90.1% in the triple drug arm (difference 9.9%, 95% CI: −0.7 to 20.7), whereas, at 48 weeks, the same proportions were 96.7% and 93.4%, respectively (difference 3.3%, 95% CI: −7.15 to 13.5). The mean change in CD4 cell count from baseline was 6.0 cells per microliter (SD, 184) for dual treatment and 16.5 cells per microliter (SD, 142) for triple treatment. A relevant decrement in CD8 + 38 + HLADR + cells was observed in both arms. The reduction was, however, significantly more pronounced in the dual-therapy arm. At week 48, the CD8 + 38 + HLADR + cell count was 3.4% (SD, 2.2) in the dual-therapy arm and 5.2% (SD, 3.1) in the triple arm ( P = 0.018). None of the patients developed severe adverse events nor had to stop treatment because of adverse events or presented grade 3–4 laboratory abnormalities. A greater reduction of bone stiffness (−2.25; SD, 7.1) was observed in patients randomized to continue triple therapy compared with patients switched to dual therapy (−0.32; SD, 8.8). Finally, baseline HIV-DNA content directly correlated with pre-cART viral load of patients ( P = 0.021), but not with time on cART or time with HIV-RNA below 50 copies per milliliter. Independently of the study arm, patients with a n HIV-RNA level constantly above 3 copies per milliliter or showing viral blips had baseline HIV-DNA levels significantly higher (64, 656 copies per 10 6 cells; SD, 93057) compared with patients who constantly presented a HIV-RNA level below the detection limit of 3 copies per milliliter (14, 457 copies per 10 6 cells; SD, 14098) ( P = 0.001). A rilpivirine-boosted plus ritonavir-boosted DRV therapy was not inferior over 48 weeks to a standard boosted protease inhibitor–based triple cART. The dual therapy did not negatively affect lipid profile and renal function and was more friendly on bone metabolism. This approach constitutes an alternative for patients experiencing nucleoside reverse transcriptase inhibitor–related toxicities.